CAR T‐cell therapy for pancreatic cancer - DeSelm, Carl J.; Tano, Zachary E.; Varghese, Anna M.; Adusumilli, Prasad S. (Journal of surgical oncology, 2017)
Chimeric antigen receptor (CAR) T‐cell therapy utilizes genetic engineering to redirect a patient's own T cells to target cancer cells. The remarkable results in hematological malignancies prompted investigating this approach in solid tumors such as pancreatic cancer. The complex tumor microenvironment, stromal hindrance in limiting immune response, and expression of checkpoint blockade on T cells pose hurdles. Herein, we summarize the opportunities, challenges, and state of knowledge in targeting pancreatic cancer with CAR T‐cell therapy.